From educational theory to professional practice: ethical reasoning in students and graduates of radiologic technology programs - Schans, Bette A., author (Colorado State University. Libraries, 2003)
The purpose of this study was to compare postconventional ethical reasoning in three groups: the student beginning an associate or baccalaureate degree radiologic technology program, the student exiting the program of study, and the radiologic technology practitioner who is three to five years post graduation. The study also examined the relationship of levels of ethical reasoning with age and formal education and compared differences in genders. The Defining Issues Test-2, developed by Rest and Narvaez, was the instrument used in this study. Participants also responded to a survey regarding expected/perceived amounts of ethical education received and evaluation of ethical behavior. Data were collected from 452 participants from radiologic technology programs in the Western United States. With one exception, there were no significant differences in levels of postconventional reasoning among beginning students, graduating students and technologist practitioners in the two types of programs. Practitioners graduating from baccalaureate programs had significant higher average postconventional scores than did practitioners graduating from associate degree programs. All groups had significant higher average scores in the maintaining norms schema than in the postconventional reasoning schema. This could indicate a propensity towards following rules rather than basing ethical decisions on developed moral reflection. A significant relationship was not found between postconventional ethical reasoning and age. Formal education was not examined due to the lack of variance in participants. Female participants averaged significant higher postconventional scores than did male participants. In 11 out of 12 contrast comparisons, there was a significant decline in perceptions of ethical education and evaluation of participant ethical behavior from beginning to graduating students to practitioners. Perceptions also were negatively correlated in relationship with age. Education in ethical theory and evaluation of ethical practice are required in radiologic technology programs. Further evaluation of educational methodology in programs across the country could be useful in explaining the results of this study.
Keywords: health education